Emerging technologies for food quality and food safety evaluation - Cho, Yong-Jin, 1961- (Contemporary food engineering., 2011)
"The evaluation of food quality and safety is one of the key tasks in the manufacturing process of foods and beverages as well as in their R&D. Even though food quality may depend on its hedonic aspect, its quantitative evaluation becomes more important in the food industry and academia. Fortunately, it is possible to definitely evaluate food quality, owing to the advent of some sophisticated systems, including nondestructive testing techniques and emerging technology. The aim of this book is to review and introduce the state-of-the-art technology and systems for quantitative evaluation of food quality, particularly those suitable for definite measurement of it. Also, this book will cover detecting systems for food safety because good foods relate directly to safe foods. This book has eleven chapters, including an introductory chapter to describe concept and scope of food quality parameters such as color, texture, shape and size, chemical compositions, flavor, safety, and so on. Chapters 2 to 11 deal with individual systems for quality parameters, i.e., instruments for textural and rheological properties, artificial intelligent systems for sensory evaluation, computer vision, near infrared (NIR), nuclear magnetic resonance (NMR) and magnetic resonance imaging (MRI), sonic and ultrasonic systems, multispectral and hyperspectral imaging techniques, electronic noses, biosensors, and nanotechnology in food quality and safety evaluation systems. Each chapter describes the principles related to each system and applications to foods"--